Development and validation of RP-HPLC method for simultaneous estimation of teneliglipt in hydro bromide hydrate and glimepiride in bulk and tablet dosage form - I.PONNILAVARASAN; N.TAMILSELVI; N.ABINAYA; R.GAYATHRI (International Journal of Pharma and Bio Sciences, 2019)
The sensitive, accurate, precise and reproducible reverse phase high performance liquid chromatography method was developed and validated for the simultaneous estimation of teneligliptinhydrobromide hydrate and glimepiride. The method was developed in reverse phase mode using Phenomenex C18 column, acetonitrile and phosphate buffer (pH 3 adjusted with orthophosphoric acid) as mobile phase in the ratio of 65:35 (v/v) at a flow rate of 1 ml/min. Quantification of drugs was achieved with ultraviolet detection at 246nm and retention time was found to be 5.8 and 9.41 min for teneligliptinhydrobromide hydrate and glimepiride respectively. The linearity was found to be in the range of 5-25 μg/ml and 0.25-1.25 μg/ml and recovery were found to be 99.80% and 99.68% teneligliptinhydrobromide hydrate and glimepiride respectively. The limit of detection (LoD) for teneligliptinhydrobromide hydrate and glimepiride was found to be 1.320μg/mL and 3.561μg/mL respectively. The limit of quantitation (LoQ) was found at 0.903μg/mL and 2.736μg/mL respectively for Teneligliptinhydrobromide hydrate and Glimepiri de. The tailing factor for peaks of teneligliptinhydrobromide hydrate and glimepiride was less than 2% and resolution was satisfactory. The system suitability studies were carried out as specified in ICH guidelines using diffe rent parameters. These parameters include a number of theoretical plates, HETP, column efficiency, resolution and capacity factor.In this study, the optimization of mobile phase, flow rate, injection volume and wavelength were achieved. All the results were validated successfully according to ICH guidelines. The developed method is eco-friendly and the peaks were more resolved when compared to the previous literatures. The developed reverse phase high performance liquid chromatography method was found to be specific since there was no co-eluting peak with drug. The developed method can be applied successfully for the assay of teneligliptinhydrobromide hydrate (TENE) an d glimepiride (GLI) of other combined pharmaceutical dosage forms available in market.